2018
DOI: 10.1007/s40620-018-0529-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the impact of older age on outcome in chronic kidney disease of different etiologies: a prospective cohort study

Abstract: BackgroundIn older patients with chronic kidney disease (CKD), the risk of progression to end stage renal disease and cardiovascular death both differ compared to younger patients. This likely reflects differences in case mix and co-morbid burdens. We sought to establish the extent to which age itself is an independent biomarker of adverse outcome in CKD.MethodsThis was an analysis of the Salford Kidney Study, a prospective, longitudinal, observational study of 2,667 patients with eGFR < 60 ml/min/1.73 m2. Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 27 publications
0
10
0
1
Order By: Relevance
“…This finding may be explained, in part, by the underdiagnoses of these comorbidities in the Medicaid cohort due to underappropriation of resources in the preoperative period for these at-risk patients. However, these findings may also be explained by the sheer age difference between the two different cohorts—both cardiac and renal comorbidity burden tend to exponentially increase as patients age [ [13] , [14] , [15] ]. Despite this, these findings should call for additional and more extensive preoperative evaluation of publicly insured patients.…”
Section: Discussionmentioning
confidence: 99%
“…This finding may be explained, in part, by the underdiagnoses of these comorbidities in the Medicaid cohort due to underappropriation of resources in the preoperative period for these at-risk patients. However, these findings may also be explained by the sheer age difference between the two different cohorts—both cardiac and renal comorbidity burden tend to exponentially increase as patients age [ [13] , [14] , [15] ]. Despite this, these findings should call for additional and more extensive preoperative evaluation of publicly insured patients.…”
Section: Discussionmentioning
confidence: 99%
“…The ESRD risk diminished with aging except in patients between 65 and 75 years with eGFRs of 25-35 mL/min per 1.73 m 2 , and in patients up to 85 years with an eGFR <15 mL/min per 1.73 m 2 [ 21 ]. In the United Kingdom, a prospective observational study comparing the impact of old age on outcomes in 2,667 CKD patients with eGFR <60 mL/min/1.73 m 2 found those under 55 years had higher risk of renal replacement therapy (RRT) than death, compared to those >75 years [ 22 ]. Consistent with the above results, we have observed that among 430 patients with stage 3-5 CKD, those aged between 20-39 years and 40-64 years, compared to ≥75 years, exhibited a higher risk of ESRD.…”
Section: Renal Aging Versus Kidney Diseasementioning
confidence: 99%
“…Indeed, it has been demonstrated that earlier stages of CKD in the elderly are more likely due to age-associated decline in glomerular filtration than real kidney disease [19]. Some studies even suggest older people with CKD may exhibit slower progression and better outcomes [20][21][22][23]. For example, in the United States, among patients with eGFR levels <45 mL/min per 1.73 m 2 , older patients were less likely to have an annual decline in eGFR of >3 mL/min per 1.73 m 2 compared to younger patients [20].…”
mentioning
confidence: 99%
“…Identifying CKD allows treat it, and the interventions are effective at any age. This is true either for causal therapy or for the overall therapy of CKD [ 44 ]. Interestingly, many treatable conditions underlying CKD are recognized in the elderly population provided that they are carefully searched for (Table 3 ).…”
Section: Diagnosing Chronic Kidney Disease In the Elderlymentioning
confidence: 99%